Trinity College Dublin Medieval and Renaissance Manuscripts - O'Mahony, Felicity (Trinity College Dublin, 2007)
The Manuscripts Department in Trinity College Library houses an internationally-renowned body of medieval manuscripts. At the heart of the Collection are the early Christian manuscripts dating from the seventh to ninth centuries: the Book of Kells, Book of Durrow, Book of Armagh, Book of Mulling, Book of Dimma, Usserianus Primus and the Garland of Howth. A wealth of material, spanning the ninth to sixteenth centuries, exists alongside these treasures. Many of these codices originally belonged to James Ussher, archbishop of Armagh, and were donated to the Library in 1661 as part of its first great benefactions. Marvin L. Colker, professor emeritus of Classics at the University of Virginia, began cataloguing the Latin manuscripts at Trinity College Library in 1958. His two-volume work Trinity College Library Dublin, Descriptive Catalogue of the Mediaeval and Renaissance Latin manuscripts, describing over four hundred and fifty manuscripts, was published in 1991. This collection continues to grow: Marvin Colker's forthcoming Supplement to the catalogue (Four Courts Press 2007/2008) contains descriptions of thirty-four manuscripts acquired by the Manuscripts Department from 1990 to 2003, as well as corrigenda and addenda to his 1991 catalogue. Among these recent acquisitions are a leaf from a service book (Italy, c.900), a register of Clairvaux Abbey (France, c.1600), and Michael of Belluno's handbook for confessors (Italy, c.1400).
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Medieval manuscripts; Renaissance manuscripts; Manuscripts Collection, Trinity College Library Dublin